Facilitation and Some of its Contemporary Applications in the Perspective of Islamic Economics - Alwan , Yasser (Islamic Sciences Journal, 2023)
ABSTRACT This research highlights some of the contemporary applications of facilitation in the perspective of Islamic economics. There is not any religious obligation or ritual in Islamic law out of breadth, ease, and evidence of Allah. There are lot of evidences in the jurisprudence of the acts of worship, treatment and the like. The Islamic economy system is nothing but an extension of the general Islamic jurisprudence. My research spoke about highlighting the quality of facilitation in the perspective of Islamic economics through explaining its contemporary applications, and the researcher has inferred evidences from the excellent sources of Islamic Sharia to support and sustain the objectives of the research. Finally, it was found that the facilitation trait is inherent in the Islamic economic system and this trait is associated with the continuous development and growth and keeping pace with the developments of the modern era.